Endoplasmic Reticulum Associated Aminopeptidase 2 (ERAP2) Is Released in the Secretome of Activated MDMs and Reduces in vitro HIV-1 Infection - Saulle, Irma; Ibba, Salomè Valentina; Torretta, Enrica; Vittori, Cecilia; Fenizia, Claudio; Piancone, Federica; Minisci, Davide; Lori, Elisa Maria; Trabattoni, Daria; Gelfi, Cecilia; Clerici, Mario; Biasin, Mara (Frontiers in Immunology, 2019)
BACKGROUND Haplotype-specific alternative splicing of the endoplasmic reticulum (ER) aminopeptidase type 2 (ERAP2) gene results in either full-length (FL, haplotype A) or alternatively spliced (AS, haplotype B) mRNA. HapA/HapA homozygous (HomoA) subjects show a reduced susceptibility to HIV-1 infection, probably secondary to the modulation of the antigen processing/presenting machinery. ERAP1 was recently shown to be secreted from the plasma membrane in response to activation; we investigated whether ERAP2 can be released as well and if the secreted form of this enzyme retains its antiviral function. METHODS Human monocyte derived macrophages (MDMs) were differentiated from peripheral blood mononuclear cells (PBMCs) isolated from 6 HomoA healthy controls and stimulated with IFN and LPS. ERAP2-FL secretion was evaluated by mass spectrometry. PBMCs (14 HomoA and 16 HomoB) and CD8-depleted PBMCs (CD8-PBMCs) (4 HomoA and 4 HomoB) were in vitro HIV-infected in the absence/presence of recombinant human ERAP2-FL (rhERAP2) protein; p24 viral antigen quantification was used to assess viral replication. IFN and CD69 mRNA expression, as well as the percentage of perforin-producing CD8+ T Lymphocytes were analyzed 3 and 7-days post in vitro HIV-1-infection respectively. The effect of rhERAP2 addition in cell cultures on T cell apoptosis, proliferation, activation and maturation was evaluated as well on 24h-stimulated PBMCs. RESULTS ERAP2 can be secreted from human MDMs in response to IFN/LPS stimulation. Notably, the addition of rhERAP2 to PBMC and CD8-PBMC cultures resulted in the reduction of viral replication, though these differences were statistically significant only in PBMCs (p< 0.05 in both HomoA and HomoB). This protective effect was associated with an increase in IFN and CD69 mRNA expression and in the percentage of perforin-expressing CD107+CD8+ cells. RhERAP2 addition also resulted in an increase of CD8+ activated lymphocyte (CD25+HLA-DRII+) and of Effector Memory/Terminally differentiated CD8+ T cells ratio. CONCLUSIONS This is the first report providing evidence for the release of ERAP2 in the secretome of immunocompetent cells. Data herein also indicate that exogenous ERAP2-FL exerts its protective function against HIV-1 infection, even in HomoB subjects who do not genetically produce it. Presumably, this defensive extracellular feature is only partially dependent on immune system modulation.